Isolation, characterization and biological activities of verotetrone from a mutant strain of Streptomyces aureofaciens - Prikrylová, V; Podojil, M; Hilgert, I; Fuska, J; Vokoun, J; Vanĕk, Z (Folia microbiologica, 1980)
A new metabolite denoted as verotetrone was isolated from the mycelium of the mutant strain Streptomyces aureofaciens NMG-2. Interpretations of physical data concerning verotetrone and its triacetate and, the determination of its degradation product indicate that verotetrone belongs to pretetramide-type metabolites. Verotetrone exhibits neither antibacterial nor antifungal activity. In vitro it inhibits the synthesis of nucleic acids as well as proteins in Ehrlich ascites carcinoma cells. Both verotetrone and its triacetate interfere in vivo with the metabolism of tumour and lymphoid cells, exhibiting antitumour or immunosuppressive activity. This activity, which is more intense with verotetrone than with its triacetate, is detectable in a dose which is already toxic in some animals.
Keywords: Anthracyclines; Ehrlichův tumor; Bacteria; experimentální leukemie; nukleové kyseliny; Carcinoma, Ehrlich Tumor; Leukemia, Experimental; experimentální nádory; Transplantation Immunology; Naphthacenes; mutace; Streptomyces aureofaciens; Mice; Mice, Inbred Strains; transplantační imunologie; inbrední kmeny myší; ženské pohlaví; Mutation; zvířata; Antibiotics, Antineoplastic; naftaceny; Neoplasms, Experimental; myši; Nucleic Acids; antracykliny; protinádorová antibiotika; Female; Candida; Animals